2009
DOI: 10.1063/1.3079078
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled GaN hexagonal micropyramid and microdisk

Abstract: The self-assembled GaN hexagonal micropyramid and microdisk were grown on LiAlO2 by plasma-assisted molecular-beam epitaxy. It was found that the (0001¯) disk was established with the capture of N atoms by most-outside Ga atoms as the (1×1) surface was constructing, while the pyramid was obtained due to the missing of most-outside N atoms. The intensity of cathode luminescence excited from the microdisk was one order of amplitude greater than that from M-plane GaN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…It is noted that the thinness of the hexagonal microdisk structure leads to an angle of 73 o off the c-axis in Fig. 4(a), which is much greater than the angle of GaN microdisk, 5 obtained from the lateral over-growth along the (1100) direction for each unit step-layer by one d M -spacing,…”
Section: Analyses and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noted that the thinness of the hexagonal microdisk structure leads to an angle of 73 o off the c-axis in Fig. 4(a), which is much greater than the angle of GaN microdisk, 5 obtained from the lateral over-growth along the (1100) direction for each unit step-layer by one d M -spacing,…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…In our previous paper, we showed that the GaN (0001) microdisk with a tilted angle of 28 o was established with the capture of N atoms by the β-dangling bonds of the most-outside Ga atoms for each unit step-layer during the GaN lateral over-growth. 5 In the case of InN microdisk, when the growth temperature lowered to 470 o C, the c-plane InN (0001) hexagonal thin disk was built up with the capture of N atoms by the β-dangling bonds of the most-outside In atoms and then the lateral over-growth occurred; capture of In atoms by β-dangling bonds of N atoms, to form the thin microdisk. The lateral over-growth along the (1100) direction was extended to six d M -spacings for each unit step-layer (i.e., thin disk in Fig.…”
Section: Analyses and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the thermal radiation will generate heat to degrade the performance and lifetime of the LED. In 2009, Ikai Lo et al developed a self-assembling nanotechnology to grow a three-dimensional (3D) hexagonal In x Ga 1-x N/GaN-microdisk from a nanometer-scaled nucleation on LiAlO 2 substrate for the application of white-light micro-LED without any assistance of phosphors [13,14]. The phosphor-free white-light micro-LEDs will benefit greatly by a high luminous efficiency and avoid the thermal aging by rare-earth doped phosphors.…”
Section: Nanotechnology and Fabrication Of Gan Crystalmentioning
confidence: 99%